A lead-isotope database of copper ores from the Southeastern Alps: A tool for the investigation of prehistoric copper metallurgy. (November 2016) - Artioli, G.; Angelini, I.; Nimis, P.; Villa, I.M.
Abstract: The Southeastern Alps were an important source of copper metal in prehistory, at least from the Eneolithic and through the Bronze Age, as documented by the abundant and substantial presence of smelting slags. Evidence of mining activity is scarce, because of limited ad hoc investigation and because of the subsequent systematic erasing by post-Medieval exploitation. Moreover, until recently the profusion of archaeometallurgical and archaeological investigations focusing on the prehistoric exploitation of Northern Alpine, Central European, and Balkan ore sources has somehow obscured the early role of the Italian Southern Alps as a major copper producing area. The recent advances in the systematic characterization of the copper ores in the Southeastern Alps (including Alto Adige, Trentino, Veneto, and nearby regions) by lead isotope analysis, supported by mineralogical and geochemical interpretation, offer now the appropriate tools to re-evaluate the extent of prehistoric mining and the local patterns of ore exploitation. The developed database is a powerful tool to identify the metal derived from local production. It is suggested that (1) based on the abundance and chronological distribution of smelting slags evidence, two major periods of mining exploitation took place, the first in the middle of the 3rd millennium BC and the second during the Late Bronze Age; and (2) based on the discrimination of copper sources and the available analyses, most of the metal circulating in Northern Italy and in the greater Po Valley region was actually produced from Southern Alpine ores. Highlights: LI data of copper ores from the South-Eastern Alps are presented and interpreted. The database of Alpine LI data is a powerful tool for provenancing ancient metal objects. Case studies include Eneolithic objects and Middle Bronze Age swords.